Pengaruh Pertumbuhan Ekonomi, Pertumbuhan Penduduk, dan Inflasi terhadap Jumlah Penduduk Miskin di Provinsi Bali Periode 1999 – 2013 - Sari, Novi Astika; Natha, Ketut Suardhika (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2017)
Poverty is a problem faced by developing country like Indonesia. One of goal national development is to decrease poverty level. This study aims to analyze the effect of economic growth, inhibitant growth and inflation both partially and simultaneously toward number of poor inhibitant at Bali province period of 1999-2013. Type of data is secondary with time series method. Analysis technique has been applied that multiple regression analysis. The result shows economic growth have negative and significant effect toward number of poor inhibitant at Baliprovince period of 1999 – 2013, inhibitan growth have positive and significant effect toward number of poor inhibitant at Bali province period of 1999-2013 and economic growth, inhibitant growth,  inflation simultaneously have effect toward number of poor inhibitant at Bali province period of 1999-2013.
Keywords: Pertumbuhan Ekonomi, Pertumbuhan Penduduk, Inflasi, Jumlah Penduduk Miskin